Kunjungan Bupati Bekasi Sebagai Ajang Penyampaian Aspirasi dan Apresiasi Pariwisata di Desa Kertarahayu - Ali, Muhammad Farhan (Rumah Jurnal UNEJ, 2022)
Several years ago, perhaps there were still many people who did not know Kertarahayu Village, located in Setu District, Bekasi Regency, West Java. However, thanks to the hard efforts & struggles of all regional apparatus and elements of society in Kertarahayu Village, finally this village began to sound echo and also succeeded in developing several important places into tourist attractions as well as valuable assets for Kertarahayu Village. This also encourages a lot of appreciation that comes from the Regional Apparatus, especially in Setu Subdistrict and Bekasi Regency. When the Bekasi Regent visited Kertarahayu Village as part of the Gebyar Desa event, they all gave feedback regarding the condition of Kertarahayu Village and also related to the activities carried out to realize the existence of Kertarahayu as one of the best tourist villages in Bekasi Regency. Don't forget to convey hope for Kertarahayu Village. In addition, there are also aspirations that come from the village community which describes infrastructure development & also the condition of tourism in this area